Korelasi Dukungan Sosial Orang Tua Pada Kepercayaan Diri RemajaPada Siswa Kelas IX SMP Negeri 1 Kalasan - Wahyuningsih, Cristina; Purbaning, Prias Hayu (SOLUTION, 2023)
The purpose of this for: 1) know of a level of teenage confidence, 2) know of a parent's level of social support, and 3) know of a parent's social correlation to the confidence of the youth. The study uses a corelational quantitative method. The subject of this study is 1 kalasan class of 55 students in the world junior high school. Data collection uses a scale based on aspects of parental social support and self-confidence. In the aspect of the parent's social support there are 22 valid items and no invalid ones. Whereas in the aspect of confidence there are 32 valid items and 3 invalid items. Research indicates that (1) a parent's social support level is at an extremely high level of 47% or 26 students, (2) a confidence level of 76% or 42 students, (3) a linear, significant, and data gathering tool in research using the social support and confidence scale, Results show (r) 0.499 and p value of 0,000 (p 0.05) that there is a significant positive relationship between the social support of a parent and the confidence of a teenager